Relative importance of pacing strategy and mean power output in 1500-m self-paced cycling - Hettinga, F. J.; de Koning, J. J.; Hulleman, M.; Foster, C. (British Journal of Sports Medicine, 2012)
Introduction Both mean power output (MPO) and the distribution of the available energy over the race, that is, pacing strategy, are critical factors in performance. The purpose of this study was to determine the relative importance of both pacing strategy and MPO to performance.